Study on the structural behaviour of monoblock hollow-core concrete sleeper under static loading / Syed Azlan Syed Hassan - Syed Hassan, Syed Azlan (Faculty of Civil Engineering, 2000)
For several years, studies have been made to improve the using of concrete sleepers. The extensive use of concrete as a material to produce sleeper has become significance. The durability and cost of concrete are the main criteria for such selection. Concrete is also has much longer life as well as having higher lateral and longitudinal stability compare to other material. This paper is a preliminary study on the behavior of monoblock hollow-core concrete sleeper (HCS) under static loading. It will govern on the structural stability and the design condition of producing the sleeper. Since this study is one of the earliest efforts in finding alternative of producing sleeper, it will also stress on the method of testing. The most important and critical part of this paper is the theoretical approach. Much can be expected from this study. Further effort to continue the interest for such study, will stimulate the industry, as far as the railway authorities are concern. In terms of technical aspects, this study will certainly provide more rooms and space for the engineers to explore.